Meningeal Melanocytoma of the Middle Cranial Fossa: A Case Report - Iliya Valkov; Milan Mladenovski (Journal of Biomedical & Clinical Research, 2020)
The term meningeal melanocytoma was first introduced by Limas and Tio in 1972 to figure out lesions of the central nervous system that, under light microscope view, have meningioma characteristics, and ultrastructural characteristics of melanocyte neoplasm, respectively. Meningeal melanocytomas (MM) represent 0.06-0.1% of brain tumors. The annual incidence is about 1 per 10 million. This type of neoplasm is rarely seen in clinical practice. A few cases have been reported in the literature. A 62-year-old man was admitted, complaining of trigeminal pain in the area of the I and II branches of CN V on the left of his face. He underwent two surgeries in a row. First, malignant melanoma, and then meningeal melanocytoma were histologically verified. Neurological examination demonstrated hyperpigmented left iris, neuralgic pain in I and II branches of CN V, latent central hemiparesis and hemihypesthesia for the right extremities, positive Babinski reflex on the right, positive axial pathological reflexes, and partial motor aphasia.Primary intracranial meningeal melanocytoma is difficult to diagnose preoperatively because of the tumor’s non-specific clinical and neuroradiological characteristics. So electron microscopy and immunohistochemical additional diagnostic confirmation are mandatory. Immunohistochemical findings - the presence of S-100 protein, vimentin, and antimelanocyte antigen HMB-45, no reaction for EMA and ultrastructural (melanosomes in different maturation, contacts type zonula adherens) are all in favour of the histopathological diagnosis of MM. Meningeal melanocytoma is a slow-growing tumor, biologically benign, and attempts for surgical radicalism are recommended. It is not entirely clear whether a malignant transformation of these tumors is possible. The role of chemotherapy also remains questionable and has not been documented as effective.